Veterinary Medicine - Clifford, Rosemarie, author 648222 (Delhi, India : The English Press, 2012)
Veterinary medicine is the branch of science that deals with the application of medical, surgical, public health, dental, diagnostic, and therapeutic principles to non-human animals, including wildlife and domesticated animals, including livestock, working animals, and companion animals. Practitioners of veterinary medicine are known as veterinarians. In most developed countries, veterinarians are highly qualified professionals with advanced educations. Veterinary science helps human health through the monitoring and control of zoonotic disease (infectious disease transmitted from non-human animals to humans) and veterinary scientists often collaborate with epidemiologists.